2010
DOI: 10.1063/1.3481344
|View full text |Cite
|
Sign up to set email alerts
|

A search for defect related ferromagnetism in SrTiO3

Abstract: Room temperature ferromagnetic hysteresis is observed in commercial SrTiO 3 substrates purchased from a variety of suppliers. It is shown that the ferromagnetic signal comes from the unpolished surfaces. Surface impurity phases cannot be detected using either x-ray diffraction or energy dispersive x-ray spectra on the unpolished surfaces. However, a possible correlation between surface disorder (xray diffraction peak linewidth) and ferromagnetism is observed. Ar ion bombardment (10keV-90 keV) can be used to pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…These observations raise a number of scientific questions. Among these, the most important question is whether ferromagnetism, and its coexistence with a superconducting state, is an intrinsic, many-body property of a 2D electron liquid in SrTiO 3 or caused by extrinsic contributions, such as disorder, defects, or impurities [10]. Pointing to impurities as the cause are observations of ferromagnetic regions that form nonuniform patches [8] and inconsistencies in the appearance of magnetism in samples grown under the same conditions [11].…”
mentioning
confidence: 99%
“…These observations raise a number of scientific questions. Among these, the most important question is whether ferromagnetism, and its coexistence with a superconducting state, is an intrinsic, many-body property of a 2D electron liquid in SrTiO 3 or caused by extrinsic contributions, such as disorder, defects, or impurities [10]. Pointing to impurities as the cause are observations of ferromagnetic regions that form nonuniform patches [8] and inconsistencies in the appearance of magnetism in samples grown under the same conditions [11].…”
mentioning
confidence: 99%
“…This has been seen in interfacial structures 6,7 , but also in bulk and thin film , both in systems that are doped with other transition metals, but also those that are not. 1,[8][9][10][11] Recent advances in the synthesis of oxygendeficient structures have allowed for the detection, measurement and control of optically induced long-lived magnetic moments in STO, further implicating Ov 12 . Very recently is was shown than electrical gating at STO-based interfaces can be controlled to induce the appearance of magnetic moments dependent on the mobile carrier density 13 .…”
mentioning
confidence: 99%
“…However, the origin of ferromagnetism in non-magnetic oxides is still controvertial as the occurrence of ferromagnetic ordering is either by the effect of substitution/doping or the secondary phase formation of magnetic ions in the host system [1,15]. According to earlier reports, various mechanism such as oxygen vacancy, d 0 magnetism and carrier mediated ferromagnetism have been suggested to explain the origin of ferromagnetic ordering in non-magnetic oxide compounds [12,13,15,16]. It is also identified that the ferromagnetism in nanoparticles may arise due to the presence of unpaired spins on the surface [1,9].…”
Section: Introductionmentioning
confidence: 97%
“…Major challenges in spin based electronic devices are the optimization of life time stability of electron spin, the recent studies reveal the possibilities of solid state and optical spin injection in semiconducting oxide materials [4,5]. In accordance to that, various transition metal doped semiconducting oxides such as ZnO, MgO, HfO 2 , TiO 2 , SnO 2 , In 2 O 3 and ABO 3 structured materials (SrTiO 3 , BaTiO 3 and KTaO 3 ) have been widely investigated to achieve the stable spin based electronic devices [6][7][8][9][10][11][12][13][14]. However, the origin of ferromagnetism in non-magnetic oxides is still controvertial as the occurrence of ferromagnetic ordering is either by the effect of substitution/doping or the secondary phase formation of magnetic ions in the host system [1,15].…”
Section: Introductionmentioning
confidence: 98%